بلاغة الصورة الروائية في أوراق شمعون المصري لأسامة الشاذلي - شيماء السيد محمد الطوخي (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd)
يهدف هذا البحث إلى دراسة بلاغة الصورة الروائية في أوراق شمعون المصري لأسامة الشاذلي، وتحليلها وفق ما يناسبها من منهج التحليل الفني ومعطيات المنهج الأسلوبي، وعلى الرغم من غلبة النص الشعري في تأسيسه للكثير من الأنواع البلاغية، فإن البلاغيين والنقاد معظمهم لا يرون فارقًا كبيرًا بين الشعر والنثر إلا من حيث ما يقتضيه النوع الأدبي من بنى لغوية كاشفة في اختيار اللفظ وصياغة التراكيب وتشكيل الصور التي تناسبها؛ من منطلق أن اللغة لا تستمد جمالياتها من ذاتها، أي من كونها دلالات وأصواتًا وألفاظًا فحسب، وإنما تستمدها من طبيعة الجنس الأدبي الذي يتوسل بها وينتج دلالتها؛ حتى انتهوا من ذلك إلى ما يشبه التنظير بأن لكل نوع أدبي بلاغته وطرائقه الخاصة في الإبداع والقراءة والتأويل. وعليه فقد اقتضت طبيعة هذا البحث تقسيمه مبحثين تسبقهما مقدمة وتمهيد وتعقبهما خاتمة وثبت بالمصادر والمراجع. أما المقدمة فقد تحدثت فيها عن أهمية الموضوع وأسباب اختياره والدراسات السابقة عليه، وبيان منهجه وخطته، كما تناولت في التمهيد التعريف بالرواية والكاتب وبيان مفهوم الصورة الروائية، ثم توزعت الظواهر بعد ذلك على المبحثين فسيق المبحث الأول لإيضاح صورة التيه وأثرها في وصف الفضاء الروائي، أما المبحث الآخر فاهتم ببيان صورة التيه وأثرها في رسم الشخصيات، على نحو يبرز دور التعبير البلاغي في رسم الصورة الروائية للتيه بوصفه المحور الرئيس الذي تدور حوله الرواية، وبيان أثرها وفاعليتها في وصف الفضاء الروائي ورسم الشخصية.This research aims to study the rhetoric of narrative imagery in Shimon the Egyptian's Papers by Osama El-Shazly, analyzing it through the lens of artistic analysis and stylistic methodology. Although poetic texts dominate in establishing many rhetorical forms, most rhetoricians and critics see no significant difference between poetry and prose, except in the linguistic structures required by each literary genre. These structures become evident in the choice of words, phrasing, and crafting of imagery that suits the text, based on the premise that language derives its aesthetic value not from its intrinsic nature as mere meanings, sounds, and words but from the nature of the literary genre that utilizes it and generates its meanings. This has led to a quasi-theoretical conclusion that each literary genre has its own rhetoric and distinct methods of creativity, reading, and interpretation.Accordingly, the nature of this research required dividing it into two sections, preceded by an introduction and a prelude and followed by a conclusion and a bibliography.The introduction discusses the importance of the topic, the reasons for choosing it, previous studies on the subject, and the methodology and structure of the research. The prelude introduces the novel and its author, as well as the concept of narrative imagery. The two main sections then address the key phenomena: the first section examines the image of "wandering" and its impact on the description of the narrative space, while the second section focuses on the image of "wandering" and its effect on character development. This approach highlights the role of rhetorical expression in shaping the narrative imagery of "wandering," as it represents the central theme of the novel, and demonstrates its impact and effectiveness in describing the narrative space and character portrayal.